The Effectiveness of injectable platelet-rich fibrin and bone graft addition to open flap debridement for infrabony pocket therapy - Rizka Dindarini; Dahlia Herawati; Sri Pramestri Lastianny (Majalah Kedokteran Gigi Indonesia, 2022)
Various biomaterials have been utilized as additional material to help tissue regeneration in the open flap debridement (OFD) procedure. Platelet-rich fibrin (PRF) is an autologous platelet concentrate that contains many growth factors (GFs) and generally used as an additional biomaterial in OFD. However, PRF has several weaknesses, such as its consistency, which is hard to mix with another biomaterial, and its abundant sediment of regenerative cells resulted from high-speed centrifugation. Injectable Platelet Rich Fibrin (I-PRF) is one of the PRF derivatives that contain more regenerative cells. Due to the low-speed centrifugation, I-PRF has a liquid form. Certain GFs were also found in I-PRF, such as PDGF, TGF-β1, VEGF, IGF, EGF dan COL-Ia. In this study, we measured probing depth (PD), relative attachment level (RAL), and bone height as the healing parameter, to see the effectiveness of I-PRF addition and bone graft in the OFD for infrabony pocket as the aim of this study. Twenty (20) periodontal pockets were chosen (PD= 5-7 mm) and divided into OFD+I-PRF+bone graft (bg) group (group I) and OFD+PRF+bg group (group II) equally. The clinical evaluation was measured at the baseline, day-30, and day-90. Results showed that PD (p= 0.022) and RAL (p= 0.008) significantly increased in group I (PD 2.80 ± 0.42; RAL 2.50 ± 0.52) compared to group II (PD 2.10 ± 0.73; RAL 2.00 ± 0.67); however, there was no significant difference in the bone height (p= 0.194). Taken together, our data revealed that I-PRF+bg induces soft tissue regeneration in infrabony pocket treatment.